Simulation of source intensity variations from atmospheric dust for solar occultation Fourier transform infrared spectroscopy at Mars - Olsen, K.S.; Toon, G.C.; Strong, K. (Journal of molecular spectroscopy, 2016)
[Display omitted] •We simulated the effects that dust has on Fourier transform spectroscopy.•After filtering the interferogram and performing a phase correction, the spectral line depths may be recovered.•This work supports high-resolution (0.02cm−1) spectroscopy in the Martian atmosphere. A Fourier transform spectrometer observing in solar occultation mode from orbit is ideally suited to detecting and characterizing vertical profiles of trace gases in the Martian atmosphere. This technique benefits from a long optical path length and high signal strength, and can have high spectral resolution. The Martian atmosphere is often subject to large quantities of suspended dust, which attenuates solar radiation along the line-of-sight. An instrument making solar occultation measurements scans the limb of the atmosphere continuously, and the optical path moves through layers of increasing or decreasing dust levels during a single interferogram acquisition, resulting in time-varying signal intensity. If uncorrected, source intensity variations (SIVs) can affect the relative depth of absorption lines, negatively impacting trace gas retrievals. We have simulated SIVs using synthetic spectra for the Martian atmosphere, and investigated different techniques to mitigate the effects of SIVs. We examined high-pass filters in the wavenumber domain, and smoothing methods in the optical path difference (OPD) domain, and conclude that using a convolution operator in the OPD domain can isolate the SIVs and be used to correct for it. We observe spectral residuals of less than 0.25% in both high- and low-dust conditions, and retrieved volume mixing ratio vertical profile differences on the order of 0.5–3% for several trace gases known to be present in the Martian atmosphere. These differences are smaller than those caused by adding realistic noise to the spectra. This work thus demonstrates that it should be possible to retrieve vertical profiles of trace gases in a dusty Martian atmosphere using solar occultation if the interferograms are corrected for the effects of dust.